1985
DOI: 10.1029/jd090id02p03850
|View full text |Cite
|
Sign up to set email alerts
|

The effect of breaking gravity waves on the dynamics and chemical composition of the mesosphere and lower thermosphere

Abstract: The influence of breaking gravity waves on the dynamics and chemical composition of the 60‐ to 110‐km region has been investigated with a two‐dimensional dynamical/chemical model that includes a parameterization of gravity wave drag and diffusion. The momentum deposited by breaking waves at mesospheric altitudes reverses the zonal winds, drives a strong mean meridional circulation, and produces a very cold summer and warm winter mesopause, in general agreement with observations. The seasonal variations of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
598
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 769 publications
(629 citation statements)
references
References 86 publications
(76 reference statements)
28
598
3
Order By: Relevance
“…[6] Some previous model studies have proposed that the semi-annual variation of atomic oxygen and oxygen airglow is due to seasonal changes in eddy diffusion (i.e., turbulent mixing) caused by gravity wave dissipation [e.g., Garcia and Solomon, 1985]. However, those authors assumed that higher eddy diffusivity produces reduced airglow emission (by downward mixing out of the airglow region) which is opposite to what is currently believed.…”
Section: Introductioncontrasting
confidence: 50%
See 1 more Smart Citation
“…[6] Some previous model studies have proposed that the semi-annual variation of atomic oxygen and oxygen airglow is due to seasonal changes in eddy diffusion (i.e., turbulent mixing) caused by gravity wave dissipation [e.g., Garcia and Solomon, 1985]. However, those authors assumed that higher eddy diffusivity produces reduced airglow emission (by downward mixing out of the airglow region) which is opposite to what is currently believed.…”
Section: Introductioncontrasting
confidence: 50%
“…Atomic oxygen is produced through the photo-dissociation of molecular oxygen in the thermosphere, and its global distribution in the MLT region is mainly controlled by dynamical transport processes [e.g., Garcia and Solomon, 1985;Brasseur and Solomon, 1986]. The two emissions provide valuable information on dynamical variations of atomic oxygen concentration at two different altitude levels [e.g., Takahashi et al, 1995;Shepherd et al, 1995Shepherd et al, , 2005Taylor et al, 1995;McLandress et al, 1996;Yee et al, 1997;Scheer et al, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…Cogger et al (1981) studied seasonal variation using satellite data and concluded that the amplitude of the semi-annual oscillation of OI5577 rises towards higher latitude. Garcia & Solomon (1985) predicted that the amplitude decreases towards the equatorial region. Takahashi et al (1995) observed strong seasonal variation of OI5577, OH(9,4) and TOH(9,4) from 4 0 S and from 23 0 S. They concluded that the semi-annual oscillations in 23 0 S are smaller than 4 0 S.…”
Section: Discussionmentioning
confidence: 99%
“…27) ozone exhibits a bi-annual oscillation (Kyrölä et al, 2010b), with maxima at equinoxes and minima at solstices. This behavior has been explained by Garcia and Solomon (1985) by invoking the effect of enhancement of gravity waves breaking at both solstices. They transport more H 2 O from below, a source of H, OH and HO 2 radicals that initiate a catalytic cycle of ozone destruction in this region.…”
Section: Ozone Climatology In the Mesosphere-lower Thermosphere (Mlt)mentioning
confidence: 99%